Personality and alcohol expectancies discriminate alcohol consumption patterns in female college students - Pilatti, Angelina (2015)
To characterize patterns of alcohol use in a sample of Argentinean female college students according to personality traits and alcohol expectancies. Methods: Data from 298 female college students (Mage = 18.27 years; SD = 1.37 years) from the city of Cordoba, Argentina were analysed using multinomial regression. Results: Three drinking categories were identified, abstainers, moderate drinkers and regular drinkers with heavy episodic drinking, and these were differentiated by three personality traits [extraversion, disinhibition (DIS) and experience seeking (ES)] and three alcohol expectancies dimensions (sociability, risk/aggression and negative mood). Regular drinkers with heavy episodic drinking and moderate drinkers had, compared to abstainers, higher scores in extroversion and alcohol expectancies for social facilitation, and lower scores in alcohol expectancies for risk and aggression. Regular drinkers with heavy episodic drinking exhibited, compared to moderate drinkers, higher scores in ES, DIS, extroversion, alcohol expectancies for social facilitation and negative mood alcohol expectancies; as well as lower scores in risk and aggression alcohol expectancies. Conclusion: College women in Argentina with problematic alcohol drinking can be distinguished from those drinking moderately.